Consumers' intention to use e-money mobile using the decomposed theory of planned behavior - Husnil, Khatimah (2016)
The purpose of this study is to understand consumers’ behavior on their intention to use e-money mobile.The study of the intention to use e-money mobile is still at the early stage in payment transaction. The e-money mobile is a new product for payment transaction that look for massive, micro, and quick means for transaction. The model that integrates in this study is the Decomposed Theory of Planned Behaviour (DTPB). In particular, it is simultaneously assesses the determinants of consumers’ intention to use e-money mobile in Indonesia which examines twelve (12) variables. The variables are attitude, awareness, subjective norm, perceived behavioral control, perceived risk, perceived security, relative advantage, complexity, social-cultural influence, family, self-confidence, and resources facilitating conditions. Based on a sample of one thousand and three hundred (1300) respondents was selected using mall-intercept method with technique sampling multistage cluster sampling and systematic random sampling in Padang, Indonesia. The Partial Least Squares Method (PLS) series PLS 2.0 M3 for algorithm and bootstrap techniques and SPSS 18 was used to test the hypothesis that has been developed. Results show that all variables had significant positive influence on the intention to use e-money mobile excluded the awareness. The awareness has positive influence but not significant on the intention to use e-money mobile. This study contributes to improve the specific theory of DTPB that generally limited to e-Commerce, e-Banking, and others social networking. The findings give more information to the issuers about the characteristic consumers and add new knowledge for academics, practioners, bank, assurance companies, airline companies and the health sector.